IMPLEMENTATION OF QUALITY FUNCTION DEPLOYMENT (QFD) IN AGRO-INDUSTRIAL TECHNOLOGY CURRICULUM - Arief Rahmawan (Agroindustrial Technology Journal, 2017)
In essence, higher education institution has important role to embody the quality of alumnus as output. When student graduate from their school, they need to compete with other schools to find a job and need to be hired by companies. In accordance with that, the institution must design best curriculum to channel core competencies in every courses of learning process. Curriculum has essential influence to create qualified alumnus in higher education level. Quality function deployment (QFD) is a methodology to correlate between customer need and technical requirement of an organization. As an emerging higher education institution, agro-industrial technology department in University Darussalam Gontor attempts to implement QFD to propose curriculum design, which core competencies applied in every discipline. The aim of this article is to provide that quality function deployment can be applied in higher education institution as a methodology to arrange better curriculum. There is a major point to be proved which is core competencies has strong relationships with abilities students as required so they can be hired to a company, as it is needed.